AN ANALYSIS OF POLITENESS MAXIMS USED BY THE MAIN CHARACTER IN COCO MOVIE - wedndha warouw; Jenie Posumah; Maikel B. G. Sanger (SoCul: International Journal of Research in Social Cultural Issues, 2021)
This research is titled "An Analysis of Politeness Maxims Used by the Main Character in Coco Movie," this study focuses on maxims related to the politeness principle by Leech. As a result, the researchers create a problem as follows: What kinds of maxims are used in the Coco Movie? The researchers employe Leech's Theory to address the question. The descriptive qualitative approach is employed in this study. The discussions in the Coco Movie script are the source of this study's data. After examining the data, it is discovered that the Movie Coco contains five maxims. The following are the statistics: 9 tact maxims, 5 generosity maxims, 1 modesty maxim, 4 approbation maxims, and 5 agreement maxims. Furthermore, tact maxim is the most frequently used maxim in Coco’s movie since the main character in this movie is concerned more with giving benefit to people around him, by using the tact maxim the speaker shows respect to the hearer by employing the tact maxim.